CORPORATE STRUCTURES IN DEVELOPING THE AGRO-INDUSTRIAL COMPLEX - Ilya M. Pravkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses conditions in which shaping of corporate structures in the agro-industrial complex of Russia takes place, and namely: market conditions of business, total integration and concentration of production, necessity to provide the rational use of all resources, using the economy of scale while making enterprises larger and more specialized. The author analyzes organizational structures of agricultural corporations which can be characterized by specificities of functioning depending on the form of integration, such as amalgamation of several business entities with the aim of developing a closed cycle, cooperation of independent legal entities under contracts, setting-up associations of farms, etc. It was proven that the system of corporate relations in Russia is passing its development stage, thus certain efforts must be applied to enhance the corporate structure.